Tahapan Konstruksi dan Logika Struktur Rumah Adat Sa’o di Dusun Doka, Nusa Tenggara Timur - Ferdy Sabono (Universitas Sebelas Maret Surakarta, 2022)
Traditional architecture in Doka called Sa’o (traditional house) has a unique physical identity in the form of structure and construction. Even though it looks simple, the structure of the foundation, the body, and the roof is able to provide strength and stability to the building. If we are looking back to see how to build a traditional house in the past, the trial and error strategy becomes a method of logical thinking by understanding the principles of building structures. For this reason, this study aims to determine the logical thinking of structural principles by identifying all steps of construction and every structural element obtained through field observations. The results show that the form of structure and construction steps at the traditional house (Sa’o) has considered the principle of load distribution and the response to the styles that influence it. That’s why this research became more interesting as a knowledge to understand the logic of thinking of those people while creating an architectural concept.